Optimalisasi Eceng Gondok (Eichhornia Crassipes) Untuk Menetralkan Ph Dan Bau Pada Limbah Ampas Tahu - Inggrit Davira Kaysa Winanta; Kirana Dayinta S; Dania Ardiana Ulfa; Yaasinta Anindya; Denny Oktavina Radianto (Universitas Pahlawan Tuanku Tambusai, 2024)
The increase in population in Indonesia is directly proportional to existing economic activities. The main need that every human needs is food, so many food industries continue to develop. One of these industries is the tofu making industry. Many of these industries result in several problems such as unpleasant odors from waste and damage to the water ecosystem in rivers. On the other hand, the use of water hyacinth is still lacking, even though if used optimally it can be used as an ecosystem controller in water. Therefore, researchers made an innovation by using water hyacinth as a pH neutralizer and odor remover in tofu dregs liquid waste. This research method is an experiment using data from journals and the internet. Data processing is descriptive in the form of data results that are compared with materials used every day.